Burnout syndrome, anxiety, and depression symptoms among workers in radiation field - Shimaa Ibrahim Amin; Rehab S. Mahdy; Dalia A. El-Shafei; Nagda Elmasry; Hassan Eldawy; Rana MagdyAbdalla; Eman Fouad (Middle East Current Psychiatry, 2024)
Abstract Background Job burnout is defined as physical, emotional, and mental exhaustion due to persistent work stress, and it includes emotional exhaustion (EE), cynicism (CY), and reduced personal accomplishment (PA) and usually leads to symptoms of depression, lack of motivation, and decreased enthusiasm. Previous studies from different countries have suggested that job burnout, depression, and anxiety are a common work-related problems. This study aims to assess for job burnout, depression, and anxiety among radiation workers in order to investigate the effects of radiation exposure during work on the mental health. This comparative cross-sectional study was performed on 208 workers in the Egyptian Atomic Energy Authority (EAEA) and the Egyptian Nuclear and Radiological Regulatory Authority (ENRRA) at Cairo Governorate, Egypt. Study participants were divided into 2 groups: 1st group which included 104 workers among radiation field and 2nd group which included 104 workers and employees who do not often work among radiation field. Maslach Burnout Inventory Scale (MBI), Hamilton Rating Scale for Depression (HAM-D), and Hamilton Rating Scale for Anxiety (HAM-A) were used to assess for burnout, depression, and anxiety among study participants. Results The prevalence and severity of depression, anxiety, burnout, and among workers inside radiation field group were statistically significantly higher than those working outside radiation field group. Work type (WIRF) and number of working hours per week (> 40 h) were the significant risk factors for all the burnout, depression, and anxiety, while age (> 40–60 years old) was a significant predictor for depression, female gender was a significant predictor for anxiety, and both age (20–40 years old) and years of experience (≤ 10 years) were significant predictors for burnout among workers inside radiation field. Conclusions Burnout, depression, and anxiety are common among workers inside radiation field with higher prevalence and severity than those working outside radiation field. Younger age, fewer years of experience, and more working hours per week are significantly associated risk factors for burnout among workers inside radiation field.